UPAYA GURU PAI DALAM MENANAMKAN NILAI-NILAI MODERASI BERAGAMA DI SEKOLAH DASAR - Santoso, Windila; Rosa Bustam, Betty Mauli (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
This research was conducted on the basis of problems with the cultivation of values in religious moderation in primary schools The researcher took the initiative to find data on how Islamic Religious Education (IRE) teachers are trying to instil moderation values in students In this study, the researcher used a qualitative research method with data collection techniques in the form of interviews and documentation The research subjects in this study are all elements in SDN Potrojayan 3. Where the results of this research are in the form of IRE teachers' efforts in instilling religious moderation values, IRE teachers do several things, namely, providing good examples or models in attitudes, during teaching and learning activities in the classroom, when creating habituation programs, making wall magazines, and in informing and providing understanding about the importance of maintaining tolerance